2020
DOI: 10.7150/jca.48365
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA LINC01391 restrained gastric cancer aerobic glycolysis and tumorigenesis via targeting miR-12116/CMTM2 axis

Abstract: Increasing studies indicate that long noncoding RNA (lncRNA) plays a critical role in aerobic glycolysis of various tumors. However, the contribution of lncRNA in gastric cancer (GC) cell glycolysis is still poorly understood. The objective of this research was to investigate the functional role and mechanism of lncRNA long intergenic non-protein coding RNA 1391 (LINC01391) in the aerobic glycolysis and tumorigenesis of GC. Here, we report that LINC01391 was low expressed in GC tissues and cell lines. LINC0139… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…For instance, the overexpressed LINC00242 promotes the GC proliferation and aerobic glycolysis in vitro and relieves the tumorigenesis in vivo through directly targeting G6PD 19 . LINC01391 overexpression hampers the proliferation, invasion and aerobic glycolysis in vitro and tumor growth in vivo of GC, while LINC01391 knockdown shows the opposite results 20 . Overexpressed DLX6-AS1 in GC signi cantly promotes cell viability and colony formation, and then regulates aerobic glycolysis by targeting phosphoinositidedependent protein kinase 1 (PDK1) 21 .…”
Section: Discussionmentioning
confidence: 94%
“…For instance, the overexpressed LINC00242 promotes the GC proliferation and aerobic glycolysis in vitro and relieves the tumorigenesis in vivo through directly targeting G6PD 19 . LINC01391 overexpression hampers the proliferation, invasion and aerobic glycolysis in vitro and tumor growth in vivo of GC, while LINC01391 knockdown shows the opposite results 20 . Overexpressed DLX6-AS1 in GC signi cantly promotes cell viability and colony formation, and then regulates aerobic glycolysis by targeting phosphoinositidedependent protein kinase 1 (PDK1) 21 .…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have reported the close association of aberrant lncRNAs and miRNAs expressions to tumor development, including glioma [ 24 , 25 ]. lncRNA HAS2-AS1 promoted tumour progression in glioma by acting as a ceRNA [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…HCG11 modulated glioma progression through its action on the miR-496/CPEB3 axis [ 27 ]. Moreover, DLGAP1-AS1 has also been implicated in several processes involved in tumor progression [ 24 , 25 ]. However, the expression and functional role of DLGAP1-AS1 in glioma has yet to be completely characterized.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the Warburg effect is still unclear. We built a panel of 17 miRNAs [ 26 29 , 31 43 ] and 8 lncRNAs [ 29 , 30 , 32 , 35 , 36 , 43 45 ] that were previously reported to be regulators of the Warburg effect. The results indicated that GF reduced the miR-489 content in the HEK-293 cell model and a moderate dose of Cur (40 μ M) could prevent this downregulation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we first measured the levels of aerobic glycolysis and evaluated Cur's protective effects in HEK-293 cells under the condition of oscillating high glucose. After that, we built a panel of 17 miRNAs [ 26 29 , 31 43 ] and 8 lncRNAs [ 29 , 30 , 32 , 35 , 36 , 43 45 ] that were previously reported to be regulators of the Warburg effect. After a range of experiments, we found miR-489/LDHA as vital modulator axis in kidney protection of Cur administration.…”
Section: Introductionmentioning
confidence: 99%